Historical Reality in the Understanding Sociology - Karosas, Justinas (Problemos, 1987)
The understanding sociology attempts to explain the life of society not from the naturalistic but from humanistic point. However, in reality this life is far from humane, and can be humanised only theoretically. The latter circumstance determined both the emergence of the humanistically oriented sociology and its deficiencies. The understanding sociology maintains that theory can disclose the secret of social life. Thus, theory endowed with power of creating social reality. However, theory cannot explain either the historical reality or itself.